Danshensu Attenuates Diabetes Associated Cognitive Dysfunction by Markedly Reversing Oxidative Stress, Agb (Band AChE Activitys - Sunil Shukla
Background: Evidences suggest that the development of neurodegenerative dementia is accelerated by Diabetes Mellitus (DM), a chronic metabolic condition. In Diabetes Mellitus (DM), improper glucose metabolism produces glycotoxins that cause beta-amyloid peptides to build up and cause oxidative damage to neurons in the brain tissue. Aim: This investigation aims to look at the neuroprotective benefits of Danshensu on memory. Materials and Methods: Involving the behaviour model (Morris water maze) and biochemical activities (measurement of glucose, Agb(B(1-42) levels, AChE, MDA, and GSH) for acute as well as chronic conditions in STZ-induced diabetic rats at 2 doses of Danshensu namely 2 mg/kg and 5 mg/kg body weight per day. Results: Results demonstrated an improvement in learning ability in both acute and chronic level treatment. Additionally, there was an alteration in the levels of biochemical markers after treatment with Danshensu, indicating that this substance may influence transmission of cholinergic neurons and potentially alleviate cognitive impairments brought on by oxidative damage. Conclusion: Danshensu ameliorates the effects of STZ more effectively at a dose of 5 mg/kg rather than 2 mg/kg at the acute level of treatment whereas at a chronic level, both 2 mg/kg and 5 mg/kg doses demonstrate an equally significant result. Therefore, Danshensu is a potential candidate for treating hyperglycemia-induced cognitive dysfunction.s